Motivasi Dan Disiplin Kerja Sebagai Upaya Peningkatan Kinerja Asn Dinas Pendidikan Kota Tidore Kepulauan - Ambarak, Susilawaty O.; Rosdiana, Rosdiana; Yunus, Imran (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research was conducted at the Tidore Islands City Education Office. The purpose of this study was to determine what efforts were made to improve the performance and work discipline of ASN in the Tidore Islands City Education Office. The data collection techniques used by the author in this study were observation, interviews, and documentation. Then the data analysis technique used by the author in this study was descriptive qualitative, namely the collected data was processed and analyzed by describing and linking it with theories that were in accordance with the existing problems, then conclusions and suggestions were drawn. The population was all ASN employees at the Tidore Islands City Education Office, a total of 38 people. When viewed overall, the results of the study show that there has been an improvement from before where there were some employees who were already disciplined at work, however, there are still a small number of employees who still often commit disciplinary violations while working. Such as not obeying the rules of work hours, going home not according to work hours and often leaving their desks.